Avaliação prospectiva da urocortina como potencial marcador sérico de endometriose pélvica - Laura Maria Almeida Maia (2013)
Background: Accurate non-invasive diagnostic tests for endometriosis are still missing. In a previous case-control study, high plasma levels of the neuropeptide urocortin were found in women with ovarian endometrioma, along with evidence of urocortin production by the endometriotic tissue. Here, we evaluated the predictive value of plasma urocortin to detect pelvic endometriosis in symptomatic women scheduled to laparoscopy. Methods: In a prospective cohort study, 77 women with chronic pelvic pain, infertility and/or adnexal mass suggestive of ovarian endometrioma were enrolled. Preoperative blood samples were obtained in EDTA-coated tubes, centrifuged at 4ºC, and the plasma was stored at -80 ºC until extracted in C-18 chromatography column and assayed for urocortin using enzyme immunoassay (EIA). All patients underwent laparoscopy and all suspect lesions were biopsied. Plasma urocortin levels were analyzed according to the final diagnosis of endometriosis (surgical and histological) and to clinical variables such as pelvic pain and infertility. Results: The prevalence of endometriosis in the cohort was 26 cases (34%). Urocortin was detected in all plasma samples. Plasma urocortin levels were significantly higher in the women with endometriosis (median 62 pg/ml, interquartile range 51-108 pg/ml, n=26) compared to those without the disease (47 pg/ml [33-66 pg/ml], n=51), p=0.029, Mann-Whitney test. Higher plasma urocortin levels were also found in association with acyclic pelvic pain (p=0.006) and dyspareunia (p=0.003). However, there was no linear correlation between plasma urocortin and the duration or intensity of pain. ROC curve analysis identified the 90% specificity cut-off point at 101 pg/ml. This value corresponded to positive predictive value of 62% and negative predictive value of 72%. Conclusion: In this cohort, the probability of endometriosis increased from 34% (pre-test probability, or overall prevalence) to 62% (post-test probability, or positive predictive value) after a positive urocortin test. The present findings suggest that high plasma urocortin levels increase the likelihood of endometriosis in symptomatic women.